A guide to assessing cellular senescence in vitro and in vivo - González‐Gualda, Estela; Baker, Andrew G.; Fruk, Ljiljana; Muñoz‐Espín, Daniel (The FEBS journal, 2021)
Cellular senescence is a complex cell response to damage and stress that can impact the surrounding tissue. Senescent cells no longer proliferate and undergo particular phenotypic changes. However, their phenotype can be very variable, and identifying senescence remains a challenge. In this review, we provide a guide to assessing senescence confidently by describing the different biomarkers and an optimized strategy for their detection in cultures, tissues and in vivo. Cellular senescence is a physiological mechanism whereby a proliferating cell undergoes a stable cell cycle arrest upon damage or stress and elicits a secretory phenotype. This highly dynamic and regulated cellular state plays beneficial roles in physiology, such as during embryonic development and wound healing, but it can also result in antagonistic effects in age‐related pathologies, degenerative disorders, ageing and cancer. In an effort to better identify this complex state, and given that a universal marker has yet to be identified, a general set of hallmarks describing senescence has been established. However, as the senescent programme becomes more defined, further complexities, including phenotype heterogeneity, have emerged. This significantly complicates the recognition and evaluation of cellular senescence, especially within complex tissues and living organisms. To address these challenges, substantial efforts are currently being made towards the discovery of novel and more specific biomarkers, optimized combinatorial strategies and the development of emerging detection techniques. Here, we compile such advances and present a multifactorial guide to identify and assess cellular senescence in cell cultures, tissues and living organisms. The reliable assessment and identification of senescence is not only crucial for better understanding its underlying biology, but also imperative for the development of diagnostic and therapeutic strategies aimed at targeting senescence in the clinic.